Infrasonic backpulsed membrane cleaning micro-and ultrafiltration membranes fouled with alumina and yeast - Shugman, E.; Aldrich, Chris; Sanderson, R.; McLachlan, D. (South African Water Research Commission, 2013)
Membrane fouling is universally considered to be one of the most critical problems in the wider application of membrane filtration. In this research microfiltration membranes were fouled during a cross-flow filtration process, using yeast and alumina suspensions in a flat cell. Infrasonic backpulsing directly into the permeate space was then used to clean the membrane, using both permeate water and soap solutions. Ultrasonic time domain reflectometry (UTDR) was used to detect and measure the growth of fouling on membrane surfaces, during the filtration and cleaning processes. The objective of this work was to examine the efficiency of back-pulse cleaning, using different combinations of membrane materials and foulants, in flat cells. The results show that a flux value of between 60% and 95% of the clean water value can be recovered after cleaning, by using a sequence of three 6.7 Hz backpulses, each pulse being 35 s long with a peak amplitude of about 140 kPa.